Analysis of Meandered PIFA Antenna Along With DGS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To Obtaining a compact design by Integration of low frequency component with high frequency component is a challenge and it is achieved in this paper. A Planar inverted F- antenna (PIFA) in Meander structure that radiates at multiple frequencies is designed in this paper. The designed antenna structure is layered as per the pre-approved guidelines with copper (annealed) as ground, FR-4(lossy) as substrate with a loss tangent (0.02δ) and patch is made up of copper (lossy) fed with meander line feeding to reduce the size of antenna and the ground is defected using fractal structure of pattern. The designed antenna is radiated at 1.725GHz, 2.412GHz and 4.788GHz respectively and as a result to this compact size of the antenna, reflection coefficient is observed at -12.905dB, -40.958dB, -38.336dB respectively. The designed antenna works in multiple applications and covers different bands which include GSM 1800, WIMAX, Wi-Fi, 3G, 4G and future 5G applications. The proposed design has a compact dimension of 60X30X1.6mm (0.70x0.35x0.018 wavelengths at the center frequency of the lower band).